Informatics System Design for the Management of Nutritional Supplementation in Body Modelling Sports - Dan MANESCU; Mihai DOINEA (Informatică economică, 2013)
Issues regarding body modeling are debated. Facts regarding the nutrional oriented processes for body modeling are identified. The nutriments classes are presented and how the administration process is conducted based on several characteristics and which are the stages of succeeding these processes. An informatics system is designed for the management of nutritional supplementation in order to control the calories intake based on the intentisty of physical effort. The stages of development are presented, identifying optimization criteria for the security of the systems and its users.